Penggunaan Pitch Rendah pada Pemeriksaan CT Scan Kepala pada Kasus Trauma di RSUD Banyumas - Aliya Ambar Sari; Widya Mufida; Muhammad Za’im (Jurnal Kesehatan Amanah, 2025)
RSUD (Regional General Hospital) Banyumas is a healthcare institution offering radiology services, such as head CT scans for trauma cases. The application of CT scan pitch parameters is essential for generating high-quality images while reducing the radiation exposure to the patient. This study employed a descriptive qualitative methodology utilizing a case study approach. The author presents an analysis of low pitch utilization in head CT scans for trauma cases at RSUD Banyumas. The research was carried out between May and June 2025. The participants included three radiographers and one radiologist. The methods employed for data collection comprised observation, interviews, and documentation. The study results demonstrate that the CT scan procedure for head trauma at RSUD Banyumas was executed with the patient in a supine head-first position and a pitch parameter set at 0.55. Employing a lower pitch enhances image detail and noise, although with the potential for increased radiation exposure. This study concludes that appropriate pitch utilization in head trauma CT scans at RSUD Banyumas significantly affects image quality.